The Effects of Creatine snd Protein Supplements on Cystatin C and Serum Creatinine Levels Among Male Weight Training Enthusiasts Aged 20-35 Years in Surabaya Gymnasiums - Winata Yantono Widarto; Rahajoe Imam Santoso; Raden Roro Shinta Arisanti; William Sayogo; Antonius Yansen Suryadarma (CV. Inara, 2026)
Protein and creatine supplementation is commonly used to enhance resistance training performance. Long-term and high-dose intake may influence renal function through renal hyperfiltration that affect glomerular filtration rate (GFR). This study aimed to examine the association between protein and creatine supplementation and renal function assessed by estimated glomerular filtration rate (through cystatin c and creatine serum), among male resistance training practitioners in Surabaya. A quantitative analytical comparative study with a cross-sectional design was conducted. The study population consisted of males aged 20–35 years who actively engaged in resistance training. Participants were classified into supplement users and non-users. Serum cystatin C and creatinine levels were measured using an automated clinical chemistry analyzer and eGFR values were calculated using CKD-EPI equations (2012 and 2021). Statistical analyses were performed to compare eGFR values between groups. Data normality was assessed using the Shapiro–Wilk test, and between-group comparisons were conducted using independent sample t-tests. Normal data distribution was confirmed (p > 0.05). Across all CKD-EPI equations, the non-supplement group consistently demonstrated higher mean eGFR values compared with the supplement group. The magnitude of these differences was small, with Cohen’s d values ranging from 0.265 to 0.278, indicating minimal practical significance. Independent sample t-tests revealed no statistically significant differences in eGFR between supplement users and non-users using CKD-EPI 2021 (p = 0.309), CKD-EPI 2012 with race coefficient (p = 0.285), or CKD-EPI 2012 without race coefficient (p = 0.292).